2016
DOI: 10.1007/s10096-016-2584-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis, aerobic vaginitis, vaginal inflammation and major Pap smear abnormalities

Abstract: The purpose of this investigation was to evaluate the impact of the vaginal milieu on the presence of abnormal Pap smears and a positive human papilloma virus (HPV) test. A cross-sectional study was conducted between June 2014 and May 2015, evaluating the vaginal discharge by fresh wet mount microscopy and comparing these data with Pap smear findings. Wet mount slides were scored for bacterial vaginosis (BV), aerobic vaginitis (AV), presence of Candida and Trichomonas vaginalis. Cytologic evaluation was done o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 51 publications
6
57
1
4
Order By: Relevance
“…Many earlier studies have not recognized or ignored the contributing effect of AV on perinatal outcomes [25,26]. However, new culture-based studies confirmed the association between AV and preterm birth [4,27].…”
Section: Discussionmentioning
confidence: 99%
“…Many earlier studies have not recognized or ignored the contributing effect of AV on perinatal outcomes [25,26]. However, new culture-based studies confirmed the association between AV and preterm birth [4,27].…”
Section: Discussionmentioning
confidence: 99%
“…While HPV persistence is a strong predictor of HSIL and the development of cervical cancer, LSIL may instead be associated with other clinical conditions. LSIL has been associated with current chlamydia infection , trichomoniasis and bacterial vaginosis . As the number of cases of individual STIs and RTIs was low, we did not attempt to stratify individual RTIs and STIs in the binary logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, cellular atypia was significantly associated with BV‐L (9.6% against 5.7%), although some reports did not find an association between cervical cytological abnormalities and BV others observed that both HPV infection and epithelial atypia were associated with BV . There has been no study about the association of atypia along with the presence of leukocytes (in cases with BV diagnosis, as shown here).…”
Section: Discussionmentioning
confidence: 54%